Peranan Legio Maria dalam Membentuk Keluarga Katolik sebagai Ecclesia Domestica - Goretty Bulaan (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2023)
This research aims to discover the role of the Legion of Mary as a real manifestation of service, apostolate, and enthusiasm in forming a Catholic Family as Ecclesia Domestica. This research uses a qualitative descriptive method and the data collection techniques used are observation, interviews, and documentation techniques. There were eight informants in the research. Based on the research results, it was found that members of the Legion of Mary who were married carried out their duties well, namely, being a driving force in the family, by directing, educating and being role models for their own families. They carried out all these tasks with enthusiasm, service, and the apostolate they received through the Legion of Mary and then applied them in family life. So, the activities of the Legion of Mary participate in forming the Catholic Family as the Ecclesia Domestica.